BELAJAR YANG BAIK - Tatta Herawati Daulae (IAIN Padangsidimpuan, 2018)
Learning is a human activity that is very important to do and is an obligation for every Muslim man and woman. By learning will get life improvement changes, and improve one's quality. In achieving the learning outcomes above, each individual is required to learn well, namely to carry out learning activities such as listening, reading, writing, making summaries, remembering, full of concentration, thinking, practicing and memorizing, disciplined, optimistic, and praying.